2010
DOI: 10.5012/bkcs.2010.31.12.3623
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Affinity of Guanidine-rich Molecular Transporters Built on myo- and scyllo-Inositol Scaffolds: Stereochemistry Dependency

Abstract: We prepared several novel molecular transporters built on myo-and scyllo-inositol scaffolds with variations in the number of guanidine residues, linker chain lengths and patterns. Some of these transporters were found to localize in mitochondria, and the mitochondrial affinity seems to be substantially related to the scaffold stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Other scaffolds investigated by Chung and co-workers include the disaccharides lactose, sucrose, and trehalose (Figure ), the monosaccharides glucose, mannose, allose, and galactose (Figure ), and monomeric myo - and scyllo -inositols (Figure ) . Both the lactose- and sucrose-based transporters feature seven guanidinium groups tethered to the sugar through linkers of different lengths (Figure a,b).…”
Section: Guanidinoglycosides Inositol and Carbohydrate Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other scaffolds investigated by Chung and co-workers include the disaccharides lactose, sucrose, and trehalose (Figure ), the monosaccharides glucose, mannose, allose, and galactose (Figure ), and monomeric myo - and scyllo -inositols (Figure ) . Both the lactose- and sucrose-based transporters feature seven guanidinium groups tethered to the sugar through linkers of different lengths (Figure a,b).…”
Section: Guanidinoglycosides Inositol and Carbohydrate Scaffoldsmentioning
confidence: 99%
“…Derivatives of myo -inositol were found to target the mitochondria, whereas the more symmetric scyllo -inositol derivatives did not show significant mitochondrial colocalization. In addition, while all the transporters showed good affinity for brain tissues, scyllo -inositol-based transporters, unlike their myo -inositol stereoisomers, were widely distributed in all organs . It seems that although the structures of the saccharide scaffolds are closely related, several parameters need to be tuned for optimal organellar selectivity and tissue distribution.…”
Section: Guanidinoglycosides Inositol and Carbohydrate Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative intensity of each signal was recorded according to a line through cells ( Figures 3(d–f) ), supporting that G4-Nal-F has high selectivity toward mitochondria. In other studies, it was reported that compounds containing multiple guanidines showed poor localization in mitochondria or localized in several organelles in addition to mitochondria, such as lysosomes and endoplasmic reticulum (Sibrian-Vazquez et al., 2008 ; Ghosh et al., 2010 ; Hamill et al., 2016 ). Therefore, it is clear that guanidines are necessary for efficient cellular uptake, but this does not assure selective localization in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently developed several types of guanidinerich molecular carriers with high molecular weights and good water solubility that readily cross the BBB and display efficient distributions in the mouse brain [20,21]. In particular, the G8 (having eight guanidine groups) molecular carrier based on carbohydrate, such as sorbitol, was found to be very effective in delivering conjugated drugs to mouse brain [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%